Analisis Kemandirian Fiskal dilihat dari Faktor-Faktor Ekonomi Daerah - Hadi Sasana (Universitas Wahid Hasyim, 2006)
Realization of a more realistic regional autonomy that can offer tangible economic, social and political benefits to the region inparticular. This research attemps to identify the influence of regional economic sectors on the Administrative Independency Ratio (Derajat Kemandirian Fiskal), in Klaten Regency. This analysis use the Partial Adjustment Model (PAM). The data used in this research are time series data for the period 1978 until 2003.The results of this research indicated that the dominant contribution for Administration Independency Ratio is coming from the agricultural sector of which the coefficient regression is 0.926 for short-term period and 1.052 for long-term period.